РЕЙТИНГУВАННЯ РОЗВИТКУ НЕДЕРЖАВНИХ ПЕНСІЙНИХ ФОНДІВ В УКРАЇНІ - Шимко, Ярослав Романович (Науковий журнал «Світ фінансів», 2019)
Шимко Я. Р. Рейтингування розвитку недержавних пенсійних фондів в Україні. Досліджено сутність рейтингування недержавних пенсійних фондів (НПФ) та акцентовано увагу на методі радара. Визначено переваги методу радара для рейтингування розвитку НПФ. Запропоновано методику обчислення інтегрального показника розвитку НПФ, на цій підставі представлено результати рейтингування найбільш розвинених НПФ в Україні. Розподілено НПФ, які функціонують, на три групи: фонди-лідери, фонди, що за лідерами, та фонди-аутсайдери. Визначено основні стратегії розвитку НПФ, що слідують за лідерами. Шимко Я. Р. Рейтингование развития негосударственных пенсионных фондов в Украине. Исследована сущность рейтингования негосударственных пенсионных фондов (НПФ) и акцентировано внимание на методе радара. Определены преимущества метода радара для рейтингования развития НПФ. Предложена методика вычисления интегрального показателя развития НПФ, на этом основании представлены результаты рейтингования наиболее развитых НПФ в Украине. Функционирующие НПФ распределены на три группы: фонды-лидеры, фонды, которые следуют за лидерами, фонды-аутсайдеры. Определены основные стратегии развития НПФ, которые следуют за лидерами. Shymko Ya. The rating of the development of non-state pension funds in Ukraine. Introduction. Rating of private pension funds (PPFs) is an instrument that provides a comprehensive understanding of the results of the activity of funds. Ratings are an important component in business information that contributes to maintaining trust in PPF activities. That’s why research into fund rating issues is an actual area of research. The purpose. The purpose of the article is to deepen the scientific and methodical approach to rating PPFs by using the radar method to calculate the integral development index of the PPF and on this basis the allocation of funds-leaders, funds that follow the leaders and funds-outsiders. Results. The interpretation of the rating results becomes objective and accurate in choosing the system of indicators that were used as the basis for the calculation of the rating, the qualitative information base, and the use of sound methodology for calculating the integrative indicator. This approach, in general, allows you to rank the PPF according to the levels of development. Scientific interest is characterized by one of the methods of benchmarking used in economic research – this is a radar method. The advantages of the radar method for rating the development of PPFs are determined. We propose to calculate the integral indicator of NPF development on the basis of quantitative indicators of development, such as net asset value, number of participants, pension contributions, pension payments, income from investing PPF assets,calculated by the expanded result since the beginning of PPF functioning. The results of the analysis of NPF development indicators in Ukraine make it possible to distinguish two main strategies for the development of funds: firstly, a strategy focused on attracting as many participants as possible; and secondly, a strategy focused on obtaining higher investment income. Conclusions. In the article, the methodical approach to the rating of PPFs in the application of the radar calculation method of the integral development index of PPFs is improved. A comparison of the radars of some domestic PPFs with reference radar for the development of funds allowed the distribution of functioning PPFs into three groups: founding foundations, follow-up funds and outsiders funds. The main strategies for the development of PPFs following the leaders were determined. The results of the PPF rating indicated that most of the funds in Ukraine have low development indicators. It actualizes the task of activating the development of domestic PPFs, in particular, in the areas of differentiation of pension products to increase the interest of citizens in participating in funds, and the development of new financial instruments to improve the results of investment activities of the PPF.